A Rare Report of Infectious Emphysematous Aortitis Secondary to Clostridium septicum without Prior Vascular Intervention - Harris, Ciel (Case Rep Vasc Med, 2017)
The term “mycotic aneurysm” was first used by Osler in 1882 to describe a mushroom-shaped aneurysm in subacute bacterial endocarditis. Mycotic aneurysms account for only 2.6% of all aneurysms of the aorta. Rarer still are anaerobic infections secondary to organisms such as Clostridium septicum, which results in emphysematous aortitis. The vast majority of emphysematous aortic infections occur as a result of instrumentation; however, in this case we present an infection de novo. A 75-year-old male presented with a 2-week history of progressive fatigue and chest pain that then developed into constitutional symptoms. Chest radiograph demonstrated an obvious widened mediastinum. CT angiogram of his chest then confirmed this finding as well as significant periaortic gas and focal outpouching. Numerous diverticuli with inflammatory changes consistent with diverticulitis was observed on CT abdomen. Blood cultures returned positive for Clostridium septicum. Definitive treatment was discussed including debridement and graft insertion; however, patient decided on conservative management and was discharged on intravenous antibiotics. Unfortunately, as in most cases of emphysematous aortitis that do not undergo surgical management, the patient succumbed to his illness. The lesson provided will be the epidemiology of emphysematous aortitis, presentation, diagnosis, management, and prognosis through a case report.